2010
DOI: 10.1038/ng.572
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis and imputation refines the association of 15q25 with smoking quantity

Abstract: Smoking is a leading global cause of disease and mortality1. We performed a genomewide meta-analytic association study of smoking-related behavioral traits in a total sample of 41,150 individuals drawn from 20 disease, population, and control cohorts. Our analysis confirmed an effect on smoking quantity (SQ) at a locus on 15q25 (P=9.45e-19) that includes three genes encoding neuronal nicotinic acetylcholine receptor subunits (CHRNA5, CHRNA3, CHRNB4). We used data from the 1000 Genomes project to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
595
3
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 585 publications
(628 citation statements)
references
References 36 publications
26
595
3
4
Order By: Relevance
“…22 The major limitation of the current study is relatively small number of CpG sites tested with pre-selection of the CpG sites, based on their relevance to cancer. Several biologically interesting candidate CpG sites such as those in the F2RL3 and the α/β nicotinic cholinergic receptors on chromosome 15q25 (i.e., determinants of smoking intensity), [5][6][7] are not included on the Cancer Panel I platform and were not evaluated in this cohort. It is therefore of future interest to assess association of other CpG sites with smoking related phenotypes and CRP level in AAT-deficient subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The major limitation of the current study is relatively small number of CpG sites tested with pre-selection of the CpG sites, based on their relevance to cancer. Several biologically interesting candidate CpG sites such as those in the F2RL3 and the α/β nicotinic cholinergic receptors on chromosome 15q25 (i.e., determinants of smoking intensity), [5][6][7] are not included on the Cancer Panel I platform and were not evaluated in this cohort. It is therefore of future interest to assess association of other CpG sites with smoking related phenotypes and CRP level in AAT-deficient subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Since tobacco smoking associates with severe airflow limitation in alpha-1 antitrypsin (aaT) deficiency and tobacco smoking are confirmed risk factors for chronic obstructive pulmonary disease. We hypothesized that variable DNa methylation would be associated with smoking and inflammation, as reflected by the level of c-reactive protein (cRp) in aaT-deficient subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Although genetic variants in genes encoding neuronal nicotinic acetylcholine receptor subunits (eg, CHRNA3 and CHRNA5) are associated with smoking quantity, the explained variances by such single-nucleotide polymorphisms are low (Tobacco and Genetics Consortium, 2010;Liu et al, 2010). This suggests that other pathways, such as the glutamatergic neurotransmission system, have a role in smoking behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The average 1975The average -2007 annual age adjusted per 100 000 incidence and mortality rates of lung cancer in African Americans was found to be 81.8 and 63.4, respectively, in comparison with 64.1 and 53.9 for European Americans (Ries et al, 2008). Recent genome-wide association studies (GWAS) have identified several genetic variants that influence nicotine intake, including a strong, replicated association between genetic variants in the chromosome 15 nicotinic receptor subunit cluster and smoking quantity in European Americans (Liu et al, 2010;Thorgeirsson et al, 2008;Thorgeirsson et al, 2010;Tobacco and Genetics Consortium, 2010).…”
Section: Introductionmentioning
confidence: 99%